Penyuluhan Terapi Relaksasi Otot Progresif untuk Mengurangi Kecemasan pada Ibu Hamil Trimester III di PMB Lina Contesa - Deby Meitia Sandy; Tri Restu Handayani (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Anxiety in third-trimester pregnant women is a common condition that may negatively affect psychological readiness for childbirth. One effective non-pharmacological intervention to reduce anxiety is progressive muscle relaxation therapy. This community service activity aimed to reduce anxiety levels among third-trimester pregnant women through health education and practical training on progressive muscle relaxation therapy. The activity was conducted at PMB Lina Contesa and involved 25 third-trimester pregnant women. The intervention consisted of health education sessions, demonstrations, and guided practice of progressive muscle relaxation therapy. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. The results showed a decrease in the mean anxiety scores after the intervention, shifting from moderate anxiety to mild anxiety levels. These findings indicate that progressive muscle relaxation therapy is effective in reducing anxiety among third-trimester pregnant women. In conclusion, health education combined with progressive muscle relaxation therapy is a safe, simple, and effective non-pharmacological approach to reduce maternal anxiety and is recommended to be integrated into antenatal care services at midwifery private practices.